A low-sensitivity fast-burning material and a preparation method thereof
Patent Information
- Application Number
- CN202611175819.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-04
- Publication Date
- 2026-10-27
AI Technical Summary
传统高能推进剂依靠CL20等高能炸药提升能量,却普遍存在机械感度极高、热点易形成、安全性差等问题,长期存在能量提升、感度恶化的矛盾,无法兼顾高能输出与本质安全
[0027]本发明所得材料常压燃速为100-400mm/s,撞击感度与摩擦感度为0-5%,该低感度速燃材料兼具高燃速与低感度的优异性能,在快速发射及可燃芯模等领域有着重要的应用潜力;且本发明制备工艺条件温和、流程简单,原料混合、包覆、模压工艺参数易控制,产品性能重复性好,便于实验室制备与工业化放大。
Abstract
Description
Technical Field
[0001] This invention relates to the field of energetic materials technology, specifically to a low-sensitivity fast-burning material and its preparation method. Background Technology
[0002] Solid rocket propellants are energetic composite materials with special functions, serving as the core power source for strategic and tactical missiles, various solid-fuel engines in spacecraft, and kinetic energy interceptors. As an important branch of chemical propellants, solid propellants are mainly divided into two categories: homogeneous propellants, represented by double-base propellants; and heterogeneous propellants, including composite solid propellants and some modified double-base propellants. The comprehensive performance of solid rocket propellants is a core indicator for evaluating the combat capability of missiles and aerospace equipment. It not only determines key tactical parameters such as range, speed, and maneuverability but also directly affects the equipment's battlefield survivability and operational safety. The general development trend of high-burning-rate solid propellants is to further improve safety performance and combustion rate. Among these, low-sensitivity, high-burning-rate solid propellants have become a key development direction in the field of solid rocket propellants. This type of propellant can significantly reduce its sensitivity to external impacts, friction, static electricity, and thermal stimuli, greatly improving the safety and reliability of the propellant throughout the entire process of production, storage, transportation, and launch. It can meet the stringent requirements of weapons and equipment such as anti-tank missiles, air defense missiles, airborne missiles, interceptor missiles, and high-speed kinetic energy projectiles for the safety and insensitivity performance of energetic materials.
[0003] To obtain low-sensitivity, high-burning-rate materials, the main approaches are to reduce the mechanical and thermal sensitivity of high-burning-rate solid propellants through material composition control, microstructure design, and interface modification. Studies by Pang Aimin, Liu Xue, and others in hydroxyl-butadiene (HbA1c) high-burning-rate propellants have found that ultrafine oxidants and conventional burning-rate catalysts can significantly increase the burning rate, but they easily exacerbate hot spot formation, leading to an increase in mechanical sensitivity. Studies by Zhang Wei, Yang Jun, and others in ultrafine AP / ferrocene catalytic systems have found that various ferrocene derivatives can significantly promote AP thermal decomposition and improve the catalytic effect of burning rate, but they also significantly exacerbate hot spot formation in the system, leading to a simultaneous increase in impact and friction sensitivity, with friction sensitivity increasing with increasing iron content in the catalyst. Based on these studies, it can be concluded that as the burning rate of a solid propellant increases, its sensitivity also increases.
[0004] Currently, high-end equipment demands a dual performance requirement for solid propellants: high burning rate and rapid response, as well as low sensitivity and high safety. Traditional high-energy propellants rely on high-energy explosives such as CL20 to increase energy, but they generally suffer from problems such as extremely high mechanical sensitivity, easy formation of hot spots, and poor safety. There has long been a contradiction between energy increase and sensitivity deterioration, making it impossible to balance high energy output and inherent safety. Research by Ren Xiaobin, Li Junqiang, and others has shown that using low-sensitivity CL20, treated with coating, eutectic, and micro / nano spheroidization to reduce sensitivity, in CMDB propellants can increase impact sensitivity to 17-24.5 (H50) / cm, but the process is complex and costly. Liu Yunjie, Zhang Tianfu, and others used bonded phase change material THP to coat fine-grained AP, and through the synergistic effect of interfacial bonding and phase change endothermic reaction, reduced impact sensitivity from 92% to 32% and friction sensitivity from 96% to 36%, but introduced additional process steps. Overseas, Wang Y et al. significantly reduced the propellant burning rate temperature sensitivity through nanocatalytic structure regulation, improving safety characteristics while maintaining high combustion performance, but this places extremely high demands on material structure design. Therefore, simultaneously improving burning rate and reducing sensitivity, overcoming the bottleneck of their mutual constraint, has significant research value and engineering significance for the rapid development of aerospace, missile weapons, and space propulsion technology.
[0005] Recently, invention patent CN106518583A disclosed a meter-scale ultra-high burning rate high-energy dense composite material and its preparation method. This material has a burning rate of over 1000 mm / s and an impact sensitivity of 44-60%, exhibiting high burning rate accompanied by high mechanical sensitivity. Regarding lightweight fast-burning materials, invention patent CN111592435B disclosed a method for preparing lightweight fast-burning materials, obtaining materials with a normal pressure burning rate of 100-1200 mm / s and a density of 0.1-1.0 g / cm³. 3 The method for producing bulk materials focuses on increasing the burning rate of the material but does not address its sensitivity. While bulk materials possess high burning rates in engine filling applications, their use is limited in the safe storage and transportation sector. Therefore, providing a low-sensitivity fast-burning material and its preparation method is a pressing technical problem that needs to be solved in this field. Summary of the Invention
[0006] To address the above problems, this invention provides a low-sensitivity fast-burning material and its preparation method.
[0007] To achieve the above objectives, the present invention adopts the following technical solution:
[0008] A low-sensitivity fast-burning material comprises the following raw materials by weight percentage: 30-40% metal powder, 35-45% fluoropolymer and 20-30% fiber material;
[0009] The metal powder is coated using fluorocarbon-modified polysiloxane composite pentaerythritol phosphate as a coating agent.
[0010] Fluorocarbon modified polysiloxane: A low surface energy lubricating layer that isolates metal powder edges and corners from friction hotspots, reducing friction sensitivity; the flexible molecular chains buffer impact forces, reducing the generation of impact hotspots; Pentaerythritol phosphate: An endothermic and flame-retardant coating component that decomposes upon heating to absorb heat and lower the temperature, inhibiting the ignition of hotspots; the phosphate groups bond with the hydroxyl groups on the surface of the metal powder, improving the adhesion of the coating layer and preventing the coating layer from falling off and failing during processing; organosilicon provides lubrication and buffering, while phosphate provides endothermic and flame-retardant properties. A single coating agent cannot simultaneously achieve dual reduction in impact and friction sensitivity; after compounding, the mechanical sensitivity can be controlled at 0-5%.
[0011] Preferably, the metal powder is composed of aluminum powder, titanium powder and copper powder, and the mass percentage of aluminum powder, titanium powder and copper powder is 70%:20%:10%.
[0012] Preferably, the fluoropolymer is composed of 60% by 40% by mass of fluororubber and polytetrafluoroethylene micropowder.
[0013] Preferably, the fiber material is composed of carbon fiber and magnesium fiber in a mass percentage ratio of 80%:20%.
[0014] Preferably, the mass ratio of fluorocarbon-modified polysiloxane to pentaerythritol phosphate in the coating agent is 7:3;
[0015] Preferably, the coating agent is 3-5% of the mass of the metal powder.
[0016] Preferably, the specific method of the coating treatment is as follows: the fluorocarbon modified polysiloxane and pentaerythritol phosphate are dissolved in ethyl ethanol to obtain a coating solution, the metal powder is added to the coating solution, stirred at 300-350 r / min for 2-4 h, then heated to 80-110℃ and kept at that temperature for 2-4 h, and then vacuum dried to obtain the coated metal powder.
[0017] The preparation method of the low-sensitivity fast-burning material described above includes the following specific steps:
[0018] (1) Weigh the raw materials according to the stated mass percentage and set aside;
[0019] (2) Fluororubber and polytetrafluoroethylene micro powder are dispersed in ethyl acetate solvent to obtain fluoropolymer. After mixing, coated metal powder, carbon fiber and magnesium fiber are added in sequence. After stirring evenly, the ethyl acetate solvent is removed to obtain material slurry. The material slurry is dried to obtain fast-burning material powder. The material powder is then molded to obtain low-sensitivity fast-burning material.
[0020] Preferably, the mixing is performed by stirring at 250-350 r / min for 3-6 h;
[0021] The mixing process involves stirring at 600-700 r / min for 1.5-3 hours.
[0022] The step of removing ethyl acetate solvent is to heat to 85°C and distill under reduced pressure.
[0023] The drying conditions are as follows: pre-drying at 60-80℃ under normal pressure for 4 hours, then transferring to a 60℃ vacuum oven for 8-12 hours until the residual solvent in the material is <0.5%;
[0024] The molding temperature is 150-180℃.
[0025] Preferably, the mass ratio of the fluororubber to the ethyl acetate solvent is 1:8 to 1:12.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] The material obtained by this invention has a burning rate of 100-400 mm / s under normal pressure and an impact sensitivity and friction sensitivity of 0-5%. This low-sensitivity fast-burning material has the excellent properties of both high burning rate and low sensitivity, and has important application potential in the fields of rapid launch and combustible core molds. Moreover, the preparation process of this invention is mild and simple, the raw material mixing, coating and molding process parameters are easy to control, the product performance has good repeatability, and it is convenient for laboratory preparation and industrial scale-up. Detailed Implementation
[0028] The following describes embodiments of the present invention. These embodiments are exemplary and intended to explain the present invention, and are not to be construed as limiting the present invention.
[0029] Raw materials:
[0030] Aluminum powder, purity: Al≥99.95%, total Fe / Si / Pb impurity content<30ppm, low oxygen type, oxygen content≤0.10%; particle size: D50=8-15μm;
[0031] Titanium powder, purity Ti≥99.90%, oxygen content≤0.12%; morphology: spherical atomized powder, D50=10-20μm;
[0032] Copper powder, with a purity of Cu≥99.98% and an oxygen content≤0.08%; particle size D50=5~10μm, spherical, and without dendritic electrolytic powder;
[0033] Fluororubber, vinylidene fluoride-hexafluoropropylene binary fluororubber (F26), raw rubber Mooney viscosity ML10 (121℃) = 40-60;
[0034] Polytetrafluoroethylene (PTFE) micro powder: purity ≥99.9%, particle size D50 = 2.5-5μm, bulk density 200-350g / L;
[0035] Short-cut carbon fiber, PAN-based short-cut carbon fiber, length 1-3mm; single filament diameter 7μm, tensile strength ≥3500MPa;
[0036] Ultrafine magnesium fiber, with a purity of Mg≥99.95% and an oxygen content≤0.15%; fiber diameter 10-30μm, length 2-4mm;
[0037] Example 1
[0038] This invention provides a method for preparing a low-sensitivity fast-burning material, specifically including the following steps:
[0039] (1) Weigh the metal powder, fluorinated polymer and fiber material according to the mass percentage ratio of 38% metal powder, 42% fluorinated polymer and 20% fiber material, wherein the metal powder is 70% aluminum powder, 20% titanium powder and 10% copper powder, the fluorinated polymer is 60% fluororubber and 40% polytetrafluoroethylene micro powder, and the fiber material is 80% carbon fiber and 20% magnesium fiber.
[0040] (2) Coating the metal powder: Fluorocarbon modified polysiloxane (1H,1H,2H,2H-perfluorooctyltriethoxysilane (PFOTS)) and pentaerythritol phosphate were mixed at a mass ratio of 7:3 and dissolved in a mixed solvent of ethanol and ethyl acetate (volume ratio of ethanol and ethyl acetate was 1:1) equal to the mass of the metal powder to prepare a coating agent solution. The amount of coating agent was 4% of the mass of the metal powder. The metal powder was added to the coating agent solution and stirred at 320 r / min for 2.5 h. Then the temperature was raised to 90 °C and kept at that temperature for 2.5 h. After vacuum drying, the coated metal powder was obtained.
[0041] (3) Disperse fluororubber and polytetrafluoroethylene micro powder in ethyl acetate solvent (the mass ratio of fluororubber to ethyl acetate is 1:8). After the fluoropolymer is fully dispersed, stir it thoroughly at 300 r / min for 4 h. Then increase the stirring speed to 650 r / min and add the coated metal powder, carbon fiber and magnesium fiber one by one. Continue stirring for 2 h until uniformly dispersed. Raise the stirring temperature to 85℃ and remove part of the solvent by vacuum distillation to obtain the material slurry. The material slurry is pre-dried at 60-80℃ under normal pressure for 4 h, and then transferred to a 60℃ vacuum oven for 8-12 h. After the solvent residue in the material is <0.5%, the fast-burning material powder is obtained. The fast-burning material powder is then molded at 170℃ to obtain a low-sensitivity fast-burning material block product with a normal pressure burning rate of 178 mm / s, a friction sensitivity of 4%, and an impact sensitivity of 2%.
[0042] Example 2
[0043] This invention provides a method for preparing a low-sensitivity fast-burning material, specifically including the following steps:
[0044] (1) Weigh the materials according to the following mass percentage ratio: 35% metal powder, 45% fluorinated polymer and 20% fiber material. The metal powder consists of 70% aluminum powder, 20% titanium powder and 10% copper powder, the fluorinated polymer consists of 60% fluororubber and 40% polytetrafluoroethylene micro powder, and the fiber material consists of 80% carbon fiber and 20% magnesium fiber.
[0045] (2) Coating the metal powder: Fluorocarbon modified polysiloxane (1H,1H,2H,2H-perfluorooctyltriethoxysilane (PFOTS)) and pentaerythritol phosphate were mixed at a mass ratio of 7:3 and dissolved in a mixed solvent of ethanol and ethyl acetate at a mass ratio of 1:1 (ethanol and ethyl acetate were in a volume ratio of 1:1). The amount of coating agent was 4% of the mass of the metal powder. The metal powder was added to the coating agent solution and stirred at 350 r / min for 3 h. Then the temperature was raised to 100 °C and kept at that temperature for 3 h. After vacuum drying, the coated metal powder was obtained.
[0046] (3) Disperse fluororubber and polytetrafluoroethylene micro powder in ethyl acetate solvent (the mass ratio of fluororubber to ethyl acetate is 1:12). After the fluoropolymer is fully dispersed, stir it thoroughly at 350 r / min for 5 h. Then increase the stirring speed to 700 r / min and add the coated modified metal powder, carbon fiber and magnesium fiber one by one. Continue stirring for 2.5 h until uniformly dispersed. Raise the stirring temperature to 85℃ and remove part of the solvent by vacuum distillation to obtain the material slurry. The material slurry is pre-dried at 60-80℃ under normal pressure for 4 h, and then transferred to a 60℃ vacuum oven for 8-12 h. After the solvent residue in the material is <0.5%, the fast-burning material powder is obtained. The fast-burning material powder is then molded at 180℃ to obtain a low-sensitivity fast-burning material block product with a normal pressure burning rate of 157 mm / s, a friction sensitivity of 2%, and an impact sensitivity of 2%.
[0047] Example 3
[0048] This invention provides a method for preparing a low-sensitivity fast-burning material, specifically including the following steps:
[0049] (1) Weigh the materials according to the following mass percentage ratio: 39% metal powder, 39% fluorinated polymer and 22% fiber material. The metal powder consists of 70% aluminum powder, 20% titanium powder and 10% copper powder. The fluorinated polymer consists of 60% fluororubber and 40% polytetrafluoroethylene micro powder. The fiber material consists of 80% carbon fiber and 20% magnesium fiber.
[0050] (2) Coating the metal powder: Fluorocarbon modified polysiloxane (1H,1H,2H,2H-perfluorooctyltriethoxysilane (PFOTS)) and pentaerythritol phosphate were mixed at a mass ratio of 7:3 and dissolved in a mixed solvent of ethanol and ethyl acetate (volume ratio of ethanol and ethyl acetate was 1:1) twice the mass of the metal powder to prepare a coating agent solution. The amount of coating agent was 4% of the mass of the metal powder. The metal powder was added to the coating agent solution and stirred at 330 r / min for 3 h. Then the temperature was raised to 100 °C and kept at that temperature for 2 h. After vacuum drying, the coated metal powder was obtained.
[0051] (3) Disperse fluororubber and polytetrafluoroethylene micro powder in ethyl acetate solvent (the mass ratio of fluororubber to ethyl acetate is 1:8). After the fluoropolymer is fully dispersed, stir it thoroughly at 260 r / min for 3.5 h. Then increase the stirring speed to 620 r / min and add the coated modified metal powder, carbon fiber and magnesium fiber one by one. Continue stirring for 1.8 h until uniformly dispersed. Raise the stirring temperature to 85℃ and remove part of the solvent by vacuum distillation to obtain the material slurry. The material slurry is pre-dried at 60-80℃ under normal pressure for 4 h, and then transferred to a 60℃ vacuum oven for 8-12 h. After the solvent residue in the material is <0.5%, the fast-burning material powder is molded at 160℃ to obtain a low-sensitivity fast-burning material block product with a normal pressure burning rate of 201 mm / s, a friction sensitivity of 3%, and an impact sensitivity of 4%.
[0052] Example 4
[0053] This invention provides a method for preparing a low-sensitivity fast-burning material, specifically including the following steps:
[0054] (1) Weigh the metal powder, fluorinated polymer and fiber material according to the mass percentage ratio of 33% metal powder, 43% fluorinated polymer and 24% fiber material, wherein the metal powder is 70% aluminum powder, 20% titanium powder and 10% copper powder, the fluorinated polymer is 60% fluororubber and 40% polytetrafluoroethylene micro powder, and the fiber material is 80% carbon fiber and 20% magnesium fiber.
[0055] (2) Coating the metal powder: Fluorocarbon modified polysiloxane (1H,1H,2H,2H-perfluorooctyltriethoxysilane (PFOTS)) and pentaerythritol phosphate were mixed at a mass ratio of 7:3 and dissolved in a mixed solvent of ethanol and ethyl acetate (volume ratio of ethanol and ethyl acetate was 1:1) twice the mass of the metal powder to prepare a coating agent solution. The amount of coating agent was 3% of the mass of the metal powder. The metal powder was added to the coating agent solution and stirred at 300 r / min for 2 h. Then the temperature was raised to 80 °C and kept at that temperature for 3.5 h. After vacuum drying, the coated metal powder was obtained.
[0056] (3) Disperse fluororubber and polytetrafluoroethylene micro powder in ethyl acetate solvent (the mass ratio of fluororubber to ethyl acetate is 1:12). After the fluoropolymer is fully dispersed, stir it thoroughly at 310 r / min for 4.5 h. Then increase the stirring speed to 660 r / min and add the coated modified metal powder, carbon fiber and magnesium fiber one by one. Continue stirring for 2.2 h until uniformly dispersed. Raise the stirring temperature to 85℃ and remove part of the solvent by vacuum distillation to obtain the material slurry. The material slurry is pre-dried at 60-80℃ under normal pressure for 4 h, and then transferred to a 60℃ vacuum oven for 8-12 h. After the solvent residue in the material is <0.5%, the fast-burning material powder is molded at 165℃ to obtain a low-sensitivity fast-burning material block product with a normal pressure burning rate of 232 mm / s, a friction sensitivity of 5%, and an impact sensitivity of 4%.
[0057] Example 5
[0058] This invention provides a method for preparing a low-sensitivity fast-burning material, specifically including the following steps:
[0059] (1) Weigh the materials according to the following mass percentage ratio: 40% metal powder, 35% fluorinated polymer and 25% fiber material. The metal powder consists of 70% aluminum powder, 20% titanium powder and 10% copper powder, the fluorinated polymer consists of 60% fluororubber and 40% polytetrafluoroethylene micro powder, and the fiber material consists of 80% carbon fiber and 20% magnesium fiber.
[0060] (2) Coating the metal powder: Fluorocarbon modified polysiloxane (1H,1H,2H,2H-perfluorooctyltriethoxysilane (PFOTS)) and pentaerythritol phosphate were mixed at a mass ratio of 7:3 and dissolved in a mixed solvent of ethanol and ethyl acetate with a volume ratio of 1:1 (ethanol and ethyl acetate were 1:1) equal to the mass of the metal powder. The amount of coating agent was 3% of the mass of the metal powder. The metal powder was added to the coating agent solution and stirred at 310 r / min for 2 h. Then the temperature was raised to 80 °C and kept at that temperature for 2 h. After vacuum drying, the coated metal powder was obtained.
[0061] (3) Disperse fluororubber and polytetrafluoroethylene micro powder in ethyl acetate solvent (the mass ratio of fluororubber to ethyl acetate is 1:12). After the fluoropolymer is fully dispersed, stir it thoroughly at 250 r / min for 3 h. Then increase the stirring speed to 600 r / min and add the coated modified metal powder, carbon fiber and magnesium fiber one by one. Continue stirring for 1.5 h until uniformly dispersed. Raise the stirring temperature to 85℃ and remove part of the solvent by vacuum distillation to obtain the material slurry. The material slurry is pre-dried at 60-80℃ under normal pressure for 4 h, and then transferred to a 60℃ vacuum oven for 8-12 h. After the solvent residue in the material is <0.5%, the fast-burning material powder is molded at 160℃ to obtain a low-sensitivity fast-burning material block product with a normal pressure burning rate of 298 mm / s, a friction sensitivity of 5%, and an impact sensitivity of 5%.
[0062] Example 6
[0063] This invention provides a method for preparing a low-sensitivity fast-burning material, specifically including the following steps:
[0064] (1) Weigh the metal powder, fluorinated polymer and fiber material according to the mass percentage ratio of 31% metal powder, 39% fluorinated polymer and 30% fiber material, wherein the metal powder is 70% aluminum powder, 20% titanium powder and 10% copper powder, the fluorinated polymer is 60% fluororubber and 40% polytetrafluoroethylene micro powder, and the fiber material is 80% carbon fiber and 20% magnesium fiber.
[0065] (2) Coating the metal powder: Fluorocarbon modified polysiloxane (1H,1H,2H,2H-perfluorooctyltriethoxysilane (PFOTS)) and pentaerythritol phosphate were mixed at a mass ratio of 7:3 and dissolved in a mixed solvent of ethanol and ethyl acetate (volume ratio of ethanol and ethyl acetate was 1:1) twice the mass of the metal powder to prepare a coating agent solution. The amount of coating agent was 5% of the mass of the metal powder. The metal powder was added to the coating agent solution and stirred at 350 r / min for 4 h. Then the temperature was raised to 110 °C and kept at that temperature for 4 h. After vacuum drying, the coated metal powder was obtained.
[0066] (3) Disperse fluororubber and polytetrafluoroethylene micro powder in ethyl acetate solvent (the mass ratio of fluororubber to ethyl acetate is 1:12). After the fluoropolymer is fully dispersed, stir it thoroughly at 280 r / min for 4 h. Then increase the stirring speed to 650 r / min and add the coated modified metal powder, carbon fiber and magnesium fiber one by one. Continue stirring for 2 h until uniformly dispersed. Raise the stirring temperature to 85℃ and remove part of the solvent by vacuum distillation to obtain the material slurry. The material slurry is pre-dried at 60-80℃ under normal pressure for 4 h, and then transferred to a 60℃ vacuum oven for 8-12 h. After the solvent residue in the material is <0.5%, the fast-burning material powder is molded at 180℃ to obtain a low-sensitivity fast-burning material block product with a normal pressure burning rate of 360 mm / s, a friction sensitivity of 4%, and an impact sensitivity of 0%.
[0067] Example 7
[0068] This invention provides a method for preparing a low-sensitivity fast-burning material, specifically including the following steps:
[0069] (1) Weigh the metal powder, fluorinated polymer and fiber material according to the mass percentage ratio of 35% metal powder, 35% fluorinated polymer and 30% fiber material, wherein the metal powder is 70% aluminum powder, 20% titanium powder and 10% copper powder, the fluorinated polymer is 60% fluororubber and 40% polytetrafluoroethylene micro powder, and the fiber material is 80% carbon fiber and 20% magnesium fiber.
[0070] (2) Coating the metal powder: Fluorocarbon modified polysiloxane (1H,1H,2H,2H-perfluorooctyltriethoxysilane (PFOTS)) and pentaerythritol phosphate were mixed at a mass ratio of 7:3 and dissolved in a mixed solvent of ethanol and ethyl acetate (volume ratio of ethanol and ethyl acetate was 1:1) twice the mass of the metal powder to prepare a coating agent solution. The amount of coating agent was 5% of the mass of the metal powder. The metal powder was added to the coating agent solution and stirred at 340 r / min for 3.5 h. Then the temperature was raised to 105 °C and kept at that temperature for 3.5 h. After vacuum drying, the coated metal powder was obtained.
[0071] (3) Disperse fluororubber and polytetrafluoroethylene micro powder in ethyl acetate solvent (the mass ratio of fluororubber to ethyl acetate is 1:8). After the fluoropolymer is fully dispersed, stir it thoroughly at 320 r / min for 4.5 h. Then increase the stirring speed to 680 r / min and add the coated modified metal powder, carbon fiber and magnesium fiber one by one. Continue stirring for 2 h until uniformly dispersed. Raise the stirring temperature to 85℃ and remove part of the solvent by vacuum distillation to obtain the material slurry. The slurry is pre-dried at 60-80℃ under normal pressure for 4 h, and then transferred to a 60℃ vacuum oven for 8-12 h. After the solvent residue in the material is <0.5%, the fast-burning material powder is obtained. The fast-burning material powder is then molded at 175℃ to obtain a low-sensitivity fast-burning material block product with a normal pressure burning rate of 389 mm / s, friction sensitivity of 0%, and impact sensitivity of 0%.
[0072] The above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A low-sensitivity fast-burning material, characterized in that, The raw materials include the following percentages by weight: 30-40% metal powder, 35-45% fluoropolymer and 20-30% fiber material; The metal powder is coated using fluorocarbon-modified polysiloxane composite pentaerythritol phosphate as a coating agent.
2. The low-sensitivity fast-burning material according to claim 1, characterized in that, The metal powder is composed of aluminum powder, titanium powder and copper powder, and the mass percentage of aluminum powder, titanium powder and copper powder is 70%:20%:10%.
3. The low-sensitivity fast-burning material according to claim 1, characterized in that, The fluoropolymer is composed of 60% by 40% by mass of fluororubber and polytetrafluoroethylene micropowder.
4. The low-sensitivity fast-burning material according to claim 1, characterized in that, The fiber material consists of carbon fiber and magnesium fiber in a mass percentage ratio of 80%:20%.
5. The low-sensitivity fast-burning material according to claim 1, characterized in that, The mass ratio of fluorocarbon-modified polysiloxane to pentaerythritol phosphate in the coating agent is 7:
3.
6. The low-sensitivity fast-burning material according to claim 1, characterized in that, The coating agent is 3-5% of the mass of the metal powder.
7. The low-sensitivity fast-burning material according to claim 1, characterized in that, The specific method of the coating treatment is as follows: the fluorocarbon modified polysiloxane and pentaerythritol phosphate are dissolved in ethyl ethanol to obtain a coating solution, the metal powder is added to the coating solution, stirred at 300-350 r / min for 2-4 h, then heated to 80-110℃ and kept at that temperature for 2-4 h, and then vacuum dried to obtain the coated metal powder.
8. The method for preparing a low-sensitivity fast-burning material according to any one of claims 1-7, characterized in that, The specific steps include the following: (1) Weigh the raw materials according to the stated mass percentage and set aside; (2) Fluororubber and polytetrafluoroethylene micro powder are dispersed in ethyl acetate solvent to obtain fluoropolymer. After mixing, coated metal powder, carbon fiber and magnesium fiber are added in sequence. After stirring evenly, the ethyl acetate solvent is removed to obtain material slurry. The material slurry is dried to obtain fast-burning material powder. The material powder is then molded to obtain low-sensitivity fast-burning material.
9. The method for preparing a low-sensitivity fast-burning material according to claim 8, characterized in that, The mixing process involves stirring at 250-350 r / min for 3-6 h. The mixing process involves stirring at 600-700 r / min for 1.5-3 hours. The step of removing ethyl acetate solvent is to heat to 85°C and distill under reduced pressure. The drying conditions are as follows: pre-drying at 60-80℃ under normal pressure for 4 hours, then transferring to a 60℃ vacuum oven for 8-12 hours until the residual solvent in the material is <0.5%; The molding temperature is 150-180℃.
10. The method for preparing a low-sensitivity fast-burning material according to claim 8, characterized in that, The mass ratio of the fluororubber to the ethyl acetate solvent is 1:8-1:12.
Citation Information
Patent Citations
Meter-level very-high-burning-rate high-energy dense composite material and preparation method thereof
CN106518583A